Validación de las escalas de evitación, ansiedad social y temor a la evaluación negativa en población colombiana (2008)
ABSTRACT: This research had the purpose of validating the Negative Fear Evaluation Scale (FNE) in Colombian population. The FNE evaluates the degree in which people experiment fear about the possibility of others judging them negatively. Likewise, this research had the purpose of validating the Social Avoidance and Distress Scale (SAD) that evaluates the subjective distress, the active avoidance or the escape desires that people with social phobia experiment. There were 471 participants of both genders, representing different social classes and educational levels. The sampling procedure was carried out at random, involved several stages and was done by conglomerates. It was found that the SAD scale showed an alpha of 0.85, whereas the FNE showed an alpha 0.66. This result raises the need to analyze reliability problems related to dichotomic inverse items and the educational level of the participants. The study suggests that psychometric evaluation instruments should use Likert scales and avoid the inclusion of reverse items.